Videoperformance Musical: uma proposta de conceituação a partir de produção autoral - Mendes, Mariana Aparecida (2023)
The technological revolution since the 20th century has generated many creative possibilities, along the access to recording devices such as cameras and smartphones, which has contributed to the increase of the number of video productions. In this context, musical videoperformance emerges as an interdisciplinary artistic language, related to musical performance, Performance Art, and audiovisual elements. Although some artistic works have already been published, there is still a lack of reflection on this concept and its creative possibilities. Therefore, this research, which is aligned with the characteristics of Art Based Research proposed by López-Cano and Opazo (2014), was developed with the aim of reflecting upon and presenting characteristics of musical videoperformance through the authorial production of four musical videoperformances produced during the research. There videoperformances are titled: Em uma nota só; Tides of Manaunaun, de H. Cowell; #E3432E; and Estudo para piano, de Tim Rescala. Within this paper, the musical videoperformances produced were organized into the two identified types: Type 1, in which there is a previously composed musical piece; Type 2, presenting unprecedented sound and visual layers created during the process. In addition, characteristic specificities of musical videoperformance were also observed in all the artworks, and a reflection on the similar and divergent aspects between the produced works was proposed. Finally, there is also a reflection on some aspects of the concept, possible research and concept developments, and additional possibilities for exploration and creation.